Accounting and the enactment of power: municipal reform by Peter Leopold 1774–1775. Issue 4 (24th May 2019) - Maran, Laura; Funnell, Warwick; Castellini, Monia
Abstract : Purpose: The purpose of this paper is to understand the enduring, fundamental contributions of accounting practices in the pursuit of decentralization by governments, with an examination of Peter Leopold's reform of the municipalities in the late eighteenth century in Italy. Design/methodology/approach: An extensive textual analysis of the very comprehensive collection of primary sources of the Grand Duchy of Tuscany during the de' Medici and Hapsburg-Lorraine's rule identified the reasons for Peter Leopold's decision to decentralize his government's authority and responsibilities. A systemic comparison of the 1765–1766 and 1775–1776 financial reports of the Municipality of Castrocaro and Terra del Sole disclosed the importance of the micro-practices of accounting and reporting for the reform. Findings: In the context of the eighteenth century enlightenment, Peter Leopold legitimized his reform by the introduction of a modern style of government based on the rationalization of the municipal administrative system and decentralization of central authority and responsibility. The reform was made feasible by the substitution of a birth right principle with an economic discourse which linked tax payments to property ownership. This had the unintended consequence of increased taxes, higher municipal expenditures and possible inequalities between municipalities. Research limitations/implications: The findings of the study are dependent on the resources which have survived and are now preserved in the official archives of Galeata and Florence. This work contributes to the extant literature on administrative reforms in a crucial period for the redefinition of sovereignty by the ruling classes, with the rise of the modern State. It extends historical understanding of the public sector with a focus on local government in the eighteenth century in a non-Anglo-Saxon context. Practical implications: The examination of the reform of Peter Leopold contributes to an enhanced understanding of present-day decentralization by governments in the context of the new public management (NPM). It provides to NPM advocates a broader temporal and contextual understanding of the impact of current decentralization reforms. Originality/value: Few accounting studies have considered the micro-aspects of decentralization reforms at the municipal level and tried to identify their impact on the wealth of the population. Moreover, Peter Leopold's reform is considered one of the most innovative and enlightened of the eighteenth century, while the remainder of Europe was still overwhelmingly committed to the centralization of administrative apparatuses. Finally, this study relates to the multi-disciplinary debate about the recognition, qualification and accountization of the impact of decentralization of responsibility for the delivery of government services.